Roscovitine, an experimental CDK5 inhibitor, causes delayed suppression of microglial, but not astroglial recruitment around intracerebral dopaminergic grafts - Tomov, Nikola; Surchev, Lachezar; Wiedenmann, Clemens; Döbrössy, Máté D.; Nikkhah, Guido (Experimental neurology, 2019)
Inhibitors of cell cycle proteins are known to reduce glial activation and to be neuroprotective in a number of settings. In the context of intracerebral grafting, glial activation is documented to correlate with graft rejection. However, the effects of modification of glial reactivity following grafting in the CNS are poorly understood. Moreover, it is not completely clear if the glial cells themselves trigger the rejection process, or are they secondarily activated. The present study investigated the effect of microglial inhibition by the cyclin-dependant kinase 5 (CDK5) inhibitor roscovitine following intracerebral transplantation in the rodent model of Parkinson's disease. Single cell suspension of rat E14 ventral mesencephalic tissue was transplanted to the dopamine-depleted striatum of unilaterally 6-hydroxydopamine (6-OHDA) lesioned male Sprague-Dawley rats. Experimental animals received injections of roscovitine (20mg/kg) or a vehicle solution three times following the procedure. Immunohistochemistry was carried out on Day 7 and Day 28 to quantitatively describe the glial reaction adjacent to grafts. The data confirm that systemic roscovitine treatment significantly reduced microglial recruitment adjacent to the grafts on Day 28, without exhibiting significant effects on astroglia. However, this was not found to correlate with elevated numbers of neurons in the grafts. Moreover, microglial reaction surrounding grafts was less pronounced compared to control animals, subjected to the mechanical influence only, even without roscovitine treatment. Our results are the first to show the effect of cell cycle inhibition in the context of neuronal transplantation. The findings suggest that microglial activation around intracerebral grafts can be modified pharmacologically. However, the results do not confirm direct neuroprotective effects of cell cycle inhibition after intracerebral transplantation. Reducing microglial recruitment around grafts could be beneficial by reducing inflammation-related degenerative processes. Sparing astrocytes in the same time provides transplanted cells with essential trophics and support. We consider microglial inhibition to be a possible approach for reducing later graft-related complications.